The Effect Of The Problem Based Learning-Based Role Playing Learning Model On Interest And Student Learning Motivation Class V SDN - Subhan Prasetio; Wahyullah Alannasir; Andi Bessa Marda (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
This research is motivated by the low learning interest and motivation of students at SDN 14 Masalima, as indicated by their limited participation in learning activities, passive behavior, and low enthusiasm toward classroom tasks. These conditions are influenced by learning fatigue, difficulties in understanding the material, and the use of conventional teaching methods that have not been able to activate students optimally. Therefore, an innovative learning model that is interactive, contextual, and capable of increasing student engagement is required. The Role Playing model combined with Problem Based Learning (PBL) is considered effective because it provides direct learning experiences through role assignments while encouraging students to solve real problems. This study aims to determine the effect of the Role Playing learning model based on PBL on the learning interest and motivation of fifth-grade students at SDN 14 Masalima. The research employed a quantitative method with a one-group pretest–posttest design involving 24 students as the research sample. Data were collected through learning interest and motivation questionnaires as well as observation sheets during the learning process. The results show that the implementation of the Role Playing model based on PBL has a significant effect on increasing students’ learning interest and motivation. Students became more active, enthusiastic, and demonstrated greater engagement throughout the learning activities. Therefore, this model is a viable alternative to improve the quality of teaching and learning processes in elementary schools.